COMPARATIVE STUDY ON ACCOUNTING AND FISCAL AMORTIZATION - MARIANA GURAU; MARIA ZENOVIA GRIGORE (Challenges of the Knowledge Society)
Placed in the international trend, Romanian accounting had experienced various changes, especially as regards of progress on disconnection between accounting and fiscality. In the present, fiscal rules should not have any role in accounting decisions, because accounting rules are applied to produce accounting information that is useful in making decisions and to provide a "true and fair view" upon financial reality of the entity. However, the barrier in the habit of accounting to thinking for fiscal point of view all economic transactions remains insurmountable, yet. Starting from this perspective on disconnection between accounting and fiscality would mean that amortization recorded in the accounting, as a result of management policy, to be different from fiscality amortization, to calculate income tax. Although formally accepted, disconnect between accounting and fiscality continues to meet many difficulties. In this sense, it is usual in practice to use the same method of amortization for accounting purposes and for fiscal purposes to prevent complications of double track amortization and prevent wandering in the rules in this field. Accounting rule is deliberately eluded in favor of the fiscal rules. This is the reason we proposed to make in this paper a comparative study between norms and rules on accounting and fiscal amortization, paper in which we intend to show the benefits of applying accounting and fiscal rules separately.